A highly robust cluster-based indium(iii)–organic framework with efficient catalytic activity in cycloaddition of CO2 and Knoevenagel condensation. Issue 11 (23rd February 2023) - Lv, Hongxiao; Fan, Liming; Hu, Tuoping; Jiao, Chenxu; Zhang, Xiutang
Abstract : The exquisite combination of [In4 (μ3 -OH)2 (COO)10 (DMF)(H2 O)2 ] clusters and H5 CPDD generated a highly robust nanoporous MOF with high catalytic performance in the cycloaddition reaction of epoxides with CO2 and Knoevenagel condensation. Abstract : The efficient catalytic performance displayed by MOFs is decided by an appropriate charge/radius ratio of defect metal sites, large enough solvent-accessible channels and Lewis base sites capable of polarizing substrate molecules. Herein, the solvothermal self-assembly led to a highly robust nanochannel-based framework of {[In4 (CPDD)2 (μ3 -OH)2 (DMF)(H2 O)2 ]·2DMF·5H2 O} n (NUC-66 ) with a 56.8% void volume, which is a combination of a tetranuclear cluster [In4 (μ3 -OH)2 (COO)10 (DMF)(H2 O)2 ] (abbreviated as In4 ) and a conjugated tetracyclic pentacarboxylic acid ligand of 4, 4′-(4-(4-carboxyphenyl)pyridine-2, 6-diyl)diisophthalic acid (H5 CPDD). To the best of our knowledge, NUC-66 is a rarely reported In4 -based 3D framework with embedded hierarchical triangular-microporous (2.9 Å) and hexagonal-nanoporous (12.0 Å) channels, which are shaped by six rows of In4 clusters. After solvent exchange and vacuum drying, the surface of nanochannels in desolvated NUC-66a is modified by unsaturated In 3+ ions, Npyridine atoms and μ3 -OH groups, all of which display polarization ability towards polar molecules due to their Lewis acidity or basicity. The catalytic experiments performed showed that NUC-66a had high catalytic activity in the cycloaddition reactions of epoxides with CO2 under mild conditions, which should be ascribed to its structural advantages including nanoscale channels, rich bifunctional active sites, large surface areas and chemical stability. Moreover, NUC-66a, as a heterogeneous catalyst, could greatly accelerate the Knoevenagel condensation reactions of aldehydes and malononitrile. Hence, this work confirms that the development of rigid nanoporous cluster-based MOFs built on metal ions with a high charge and large radius ratio will be more likely to realize practical applications, such as catalysis, adsorption and separation of gas, etc .